Contribution of Sharia Banks to the Indonesian Economy - Rizal, Fitra (Etihad: Journal of Islamic Banking and Finance, 2023)
Introduction: Banks, as financial intermediaries, have a strategic role in driving the economy. This research analyzes the influence of third-party funds and working capital financing of Sharia commercial banks on the Indonesian economy. Research Methods: The research method is quantitative by conducting multiple linear regression tests. The data type used is secondary data from 2015 to 2022, with a sample size of 13 Islamic commercial banks in Indonesia. This data was obtained from BI and OJK reports. Results: The research results show that; There is a significant influence between the Third Party Funds variable on Gross Domestic Product. There is a significant influence between the Working Capital Financing variable on the Gross Domestic Product. And together the variables Third Party Funds and Working Capital Financing have a significant influence on Gross Domestic Product. With a coefficient of determination value of 91.8 percent. Conclusion: This shows that Islamic banks have a real contribution to economic growth in Indonesia. So management and the government must improve bank performance so that the circulation of funds in banks runs smoothly, people's production activities increase, the use of labor is maximized, and ultimately the Indonesian economy improves.